The impact of a chest tube management protocol on the outcome of trauma patients with tube thoracostomy - ABREU,EMANUELLE MARIA SÁVIO DE (2015)
ABSTRACTObjective:to investigate the effect of standardized interventions in the management of tube thoracostomy patients and to assess the independent effect of each intervention.Methods:A chest tube management protocol was assessed in a retrospective cohort study. The tube thoracostomy protocol (TTP) was implemented in August 2012, and consisted of: antimicrobial prophylaxis, chest tube insertion in the operating room (OR), admission post chest tube thoracostomy (CTT) in a hospital floor separate from the emergency department (ED), and daily respiratory therapy (RT) sessions post-CTT. The inclusion criteria were, hemodynamic stability, patients between the ages of 15 and 59 years, and injury severity score (ISS) < 17. All patients had isolated injuries to the chest wall, lung, and pleura. During the study period 92 patients were managed according to the standardized protocol. The outcomes of those patients were compared to 99 patients treated before the TTP. Multivariate logistic regression analysis was performed to assess the independent effect of each variable of the protocol on selected outcomes.Results:Demographics, injury severity, and trauma mechanisms were similar among the groups. As expected, protocol compliance increased after the implementation of the TTP. There was a significant reduction (p<0.05) in the incidence of retained hemothoraces, empyemas, pneumonias, surgical site infections, post-procedural complications, hospital length of stay, and number of chest tube days. Respiratory therapy was independently linked to significant reduction (p<0.05) in the incidence of seven out of eight undesired outcomes after CTT. Antimicrobial prophylaxis was linked to a significant decrease (p<0.05) in retained hemothoraces, despite no significant (p<0.10) reductions in empyema and surgical site infections. Conversely, OR chest tube insertion was associated with significant (p<0.05) reduction of both complications, and also significantly decreased the incidence of pneumonias.Conclusion:Implementation of a TTP effectively reduced complications after CTT in trauma patients.